Respuesta :

Answer:

The expression is d(45) + 25 = c

Step-by-step explanation:

The expression is d(45) + 25 = c. Let's test it out to see if it is correct. We will test it out by substituting d and c.

Day 1:

  • For a day, the expression will be 1(45) + 25 = 70
  • => 45 + 25 = 70
  • => 70 = 70

Day 2:

  • For two days, the expression will be 2(45) + 25 = 115
  • => 90 + 25 = 115
  • => 115 = 115

Day 3:

  • For three days, the expression will be 3(45) + 25 = 160
  • => 135 + 25 = 160
  • => 160 = 160

Day 4:

  • For four days, the expression will be 4(45) + 25 = 205
  • => 180 + 25 = 205
  • =>  205 = 205

Therefore, the expression is d(45) + 25 = c.

Hoped this helped.